Safety and Dosing Study of Glucagon-Like Peptide 2 in Children With Intestinal Failure. (July 2017) - Sigalet, David L.; Brindle, Mary; Boctor, Dana; Casey, Linda; Dicken, Bryan; Butterworth, Sonia; Lam, Viona; Karnik, Vikram; de Heuvel, Elaine; Hartmann, Bolette; Holst, Jens
Background and Aims: A glucagon-like peptide 2 (GLP-2) analogue is approved for adults with intestinal failure, but no studies of GLP-2 have included children. This study examined the pharmacokinetics, safety, and nutritional effects of GLP-2 in children with intestinal failure. Methods: Native human GLP-2(1-33) was synthesized following good manufacturing practices. In an open-label trial, with parental consent, 7 parenteral nutrition–dependent pediatric patients were treated with subcutaneous GLP-2 (20 µg/kg/d) for 3 days (phase 1) and, if tolerated, continued for 42 days (phase 2). Nutritional treatment was directed by the primary caregivers. Patients were followed to 1 year. Results: Seven patients were enrolled (age: 4.0 ± 0.8 years; bowel length, mean ± SEM: 24% ± 4% of predicted). All were parenteral nutrition dependent since birth, receiving 44% ± 5% of calories by parenteral nutrition. GLP-2 treatment had no effect on vital signs (blood pressure, heart rate, and temperature) and caused no significant adverse events. Peak GLP-2 levels were 380 pM (day 3) and 295 pM (day 42), with no change in half-life or endogenous GLP-2 levels. Nutritional indices showed a numeric improvement in z scores and citrulline levels; the z score was maintained while citrulline levels returned to baseline once GLP-2 was discontinued. Conclusions: GLP-2 was well tolerated in children, with a pharmacokinetic profile similar to that of adults. There were no changes in endogenous GLP-2 release or metabolism. These results suggest that GLP-2 ligands may be safely used in pediatric patients; larger trials are suggested to investigate nutritional effects.